Canthigaster aziz, a new deep-dwelling toby fish (Tetraodontiformes: Tetraodontidae) from the Red Sea - Matsuura, Keiichi; Bogorodsky, Sergey V.; Mal, Ahmad O.; Alpermann, Tilman J. (Zootaxa, 2020)
A new species of toby fish, Canthigaster aziz, is described based on a single specimen collected from the northern Red Sea off Saudi Arabia. The holotype was trawled from a depth of 315 m, the second deepest record for the genus. The new species is distinguished from other species of the genus by the following combination of characters: 8 dorsal-fin rays; 8 anal-fin rays; 15 pectoral-fin rays; dorsal-fin origin opposite to anal-fin origin; five diffuse, saddle-like, black blotches along dark yellowish dorsal edge of body between nape and dorsal-fin origin; dorsal half of body light brown with concentrated dark pigments just behind eye and with a longitudinal, irregular, pale golden stripe running from area just behind eye to dorsal side of caudal peduncle; ventral half of posterior part of body pinkish with tiny subcutaneous black spots; head and ventral half of body before anus white; and all fins uniformly pale grey. A phylogenetic analysis of the mitochondrial COI barcoding region resulted in a new and unique evolutionary lineage for the new species that is sister to a clade composed of C. leoparda, C. pygmaea and C. valentini. It also shows C. aziz to be evolutionary deeply divergent from its closest congeners. In addition to the description of the new species, comparisons with congeners and a revised key to the Indo-Pacific species are provided.